Review on extraction of antioxidant from Hibiscus Rosa Sinensis using natural deep eutectic solvent / Dr Nor Fariza Ismail and Mimi Ayuni Mazlan - Ismail, Nor Fariza; Mazlan, Mimi Ayuni (2020)
In this Final Year Project (FYP) entittled A Revıew on Extraction of Antioxidant From Hibiscus Rosa Sinensis by Using Natural Deep Eutectic Solvent is focusing on the review from the previous articles regarding to the topic. The objective of this project is to compare the extraction method on antioxidant from the plants to be applied to Hibiscus Rosa Sinensis species from the various previous articles available. Besides, it is also to suggest the best method on extraction of antioxidant component for Hibiscus Rosa Sinensis plant. There are various types of antioxidants extraction techniques from plants that are used in many studies. In the study by Selvamuthukumaran and Shi in 2017, they divide the extraction method into conventional and non-conventional extraction. In conventional extraction, there three process approach which are soxhlet extraction, maceration, hydrodistillation. In non-conventional method, it can be divided into Ultrasound-assisted extraction (UAE), Pulsed electric field (PEF) extraction and Enzymeassisted extraction. All of the methods have its own effectiveness based on different properties to be compared. It cannot be compared into a specific range based on the specific properties. However, it is found that there is widely usage of conventional solvent in the industry. With continues consumption and large amounts of these volatile and hazardous organic solvents may yet effecting the pollution to the environment and unacceptable residues in extracts. So, by using Deep Eutectic Solvent (DES) which a non-conventional solvent is the most recommended due to the green technology and sustainability. It also green, eco-friendly, sustainable and low cost solvents that can be used as the new alternative in extraction technology the many fields.